Effect of maternal role training program based on Mercer theory on maternal self-confidence of primiparous women with unplanned pregnancy - Maryam Fasanghari; Masoumeh Kordi; Negar Asgharipour (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Maternal confidence is an extremely important factor in playing the mother's role and her identity formation. Loss of self-confidence occurs in primiparous women due to the lack of maternal skills. Obtaining the behaviors of maternal role and self-confidence, the mother provides better care for her child. Hence, the aim of this study was to examine the effect of maternal role training program based on Mercer theory on maternal self-confidence of primiparous women with unplanned pregnancy. METHODOLOGY OF THE RESEARCH: This clinical trial was performed on 67 primiparous women referring to Mashhad health centers. Individuals were randomly divided into intervention and control groups. A maternal role training program based on Mercer theory was carried out for intervention group (three sessions of group training in the 34th, 35th, and 36th weeks of pregnancy and one individual training session before discharge from the hospital and then, weekly follow-up over the phone for 4 weeks). The control group received the normal pregnancy care. The research tools were questionnaires of demographic characteristics, London, DASS 21, Edinburgh Postnatal Depression Scale, Parenting Sense of Competence, General Impressions on Infant Temperament Questionnaire, and Six Simple Questions. Maternal self-confidence was measured before training, 4 weeks after delivery, and 4 months after delivery. Data analysis was carried out using independent t-test, Chi-square test, paired t- test, Mann-Whitney test, one-way ANOVA, and Wilcoxon test. P < 0.05 was considered statistically significant. RESULTS: There was a significant difference between mean maternal self-confidence changes (before training and 4 weeks after delivery (P = 0.003) and before training and 4 months after delivery (P = 0.001) in both groups. After eliminating the effect of interventional variables, the mean scores of maternal self-confidence after training in the intervention group had a statistically significant difference with that in the control group (P = 0.001). CONCLUSIONS: Maternal role training program based on Mercer theory increases maternal self-confidence in primiparous women with unplanned pregnancy. Teaching maternal role is recommended to all health-care providers.